Self‐Assembly Construction of Carbon Nanotube Network‐Threaded Tetrathiafulvalene‐Bridging Covalent Organic Framework Composite Anodes for High‐Performance Hybrid Lithium‐Ion Capacitors. Issue 10 (11th September 2022) - Yan, Wen; Yu, Fei; Jiang, Ying; Su, Jian; Ke, Si-Wen; Tie, Zuoxiu; Zuo, Jing-Lin; Jin, Zhong
Abstract : Hybrid lithium‐ion capacitors (HLICs), a special class of electrochemical energy storage devices composed of battery‐type anodes and capacitor‐type cathodes, have the potential to bridge the gap between high‐energy‐density batteries and high‐power‐density capacitors. Nevertheless, the key challenge for developing high‐performance HLICs is the imbalances of the electrochemical kinetics and lifespans between the battery‐type anodes and capacitor‐type cathodes. Herein, the self‐assembly preparation of the 3D‐crosslinked carbon nanotube (CNT) network‐threaded tetrathiafulvalene‐bridging covalent organic framework (TTF‐COF) composite via in situ growth of the 2D‐stacked TTF‐COF capping layer alongside the outer walls of 3D‐interlaced CNTs is reported. Originated for the electron‐donating and redox‐switchable TTF units, the TTF‐COF component has abundant active sites and high charge conductivity for reversible Li + storage. Moreover, due to the 3D‐assembled architecture, the TTF‐COF/CNT composite possesses abundant open nanochannels for ion transfer and 3D‐interconnected conductive CNT network for electron transfer. When used in HLICs, the TTF‐COF/CNT composite anodes exhibit ultrahigh specific capacity (609 mAh g −1 at 100 mA g −1 ) and outstanding power density (12 000 W kg −1 at 4000 mA g −1 ). Herein, the design of advanced COF composite materials with high activity, porosity, and conductivity can be a promising route for boosting the overall performances of high‐power‐type energy storage devices. Abstract : Self‐assembly preparation of 3D‐crosslinked carbon nanotube (CNT) network‐threaded tetrathiafulvalene‐bridging covalent organic framework (TTF‐COF) composite is proposed via in situ growth of 2D‐stacked TTF‐COF capping layer alongside the outer walls of 3D‐interlaced CNTs. The TTF‐COF/CNT composite anode possesses abundant active sites for reversible Li + storage, open nanochannels for ion transfer, and 3D‐interconnected conductive CNT network for electron transfer.